NILAI-NILAI RELIGIUS ISLAM DALAM NOVEL ” DALAM MIHRAB CINTA” KARYA HABIBURRAHMAN EL-SHIRAZY - Dian Shaumia (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2020)
This study aimed to get an overview of religious values of Islam in the novel in the mihrab love Habiburrahman el -shirazy include the values of faith, sharia and morals. The formulation of the problem posed is (1) how Islamic values are reflected in the behavior of the characters in the novel in the mihrab of love, (2) how the values of sharia reflected in the behavior of the characters in the novel in the mihrab of love, (3) how values morals are reflected in the behavior of the characters in the novel in the mihrab love. the study of the theory used in this research there are six, namely (1) the nature of fiction, (2) the nature of the novel, (3) the analysis approach fiction, (4) the nature of value, (5) the nature of the Islamic religion, (6) religious values of Islam.This type of research is qualitative research is the analysis of the contents, the contents of which were excavated here is the religious values of Islam include Islamic values, Islamic morals. the method used is the method deskriptif.objek this study is novel in the mihrab love Habiburrahman el-Syirazi. Research data religious values of Islam dominant reflected in the behavior of the characters in the novel in the mihrab love Habiburrahman el-Shirazy as follows: (1) the values of the creed of Islam is to believe in a god, believing in the book of Allah, believe in the apostle, (2] values of sharia are wearing Muslim fashion, praying, reading the Koran, pilgrimage, jihad filsabillah.